Studi Laboratorium Efek Pencampuran Rumput Laut Dan Polimer Xanthan Gum Terhadap Adsorpsi - Valentyn Paul Bodywein Hattu; Deny Ismail Pellu (Department of Mechanical Engineering, 2023)
Polymer injection is an EOR method that uses a polymer solution to increase oil recovery by decreasing the oil-water mobility ratio, by increasing the viscosity of the injection water. The purpose of this study was to analyze the effect of adding seaweed to xanthan gum polymer at various concentrations. The effect that is analyzed in this study is the adsorption of the solution. From the research that has been done, it can be concluded that, based on the adsorption test, xanthan gum polymer is the best. Keywords: Polymer Injection, EOR, Adsorption